The Growth of Disability Insurance in Belgium: Determinants and Policy Implications - Octave De Brouwer; Ilan Tojerow (Institute of Labor Economics (IZA), 2023)
Between 2005 and 2020, Belgium experienced a significant rise in the recipiency rate of long-term disability insurance (DI), rising from 3.5% to 6.8%. In this paper, we examine the potential factors driving this increase by exploiting administrative micro-level data covering the Belgian population from 2005 to 2015. Our analysis reveals that changes in observable characteristics, such as age, labor market participation among some groups of workers, and several job characteristics, can only marginally account for the increase in the long-term DI entry rate between 2005 and 2015. We also find evidence suggesting that reforms in unemployment insurance over the past two decades have contributed to the rise in the DI entry rate from unemployment. Finally, drawing on the literature on optimal DI policy, we discuss potential reforms aimed at decreasing the Belgian DI recipiency rate.
Keywords: H53; H55; J65; 330; social insurance; disability insurance; unemployment insurance